Serotonin-Mediated Cardiac Analgesia via Ah-Type Baroreceptor Activation Contributes to Silent Angina and Asymptomatic Infarction. (15th July 2019) - Wen, Xin; Yu, Xue; Huo, Rong; Yan, Qiu-Xin; Wu, Di; Feng, Yan; Li, Ying; Sun, Xun; Li, Xin-Yu; Sun, Jie; Li, Ke-Xin; Li, Qing-Yuan; et al.
Abstract: Silent angina is a critical phenomenon in the clinic and is more commonly associated with women patients suffering from myocardial ischemia. Its underlying cause remains mysterious in medicine. With our recent discovery of female-specific Ah-type baroreceptor neurons (BRNs), we hypothesize that cardiac analgesia is due to the direct activation of Ah-type BRNs by elevated levels of circulating serotonin (5-HT) myocardial infarction (MI) patients. Electromyography and the tail-flick reflex were assessed in control and MI-model rats to evaluate 5-HT-mediated BP regulation as well as peripheral and cardiac nociception. 5-HT or a 5-HT receptor agonist was microinjected into the nodose ganglion to confirm the involvement of the afferent pathway of the baroreflex arc. An inward current was observed in identified BRNs by applying a whole-cell patch-clamp technique in conjunction with qRT-PCR to verify the afferent-specific action of 5-HT and the expression of 5-HT receptors. Although the tail-flick reflex and mean arterial pressure were dramatically reduced in female MI rats with elevated serum 5-HT, intrapericardial capsaicin-evoked muscular discharges were significantly inhibited in comparing with those of males, which were mimicked by microinjection of 5-HT or SR57227A into the nodose. Ah-type BRNs displayed robust inward currents at lower concentrations of 5-HT than the C-type or the A-type, with significantly increased expression and cellular distribution of 5-HT3A R but not 5-HT3B R compared to the A- and C-types. Activation of 5-HT3A R in Ah-type BRNs by 5-HT contributes significantly to cardiac analgesia, which may suggest the pathogenic condition that silent angina occurs mainly in female patients. Highlights: 5-HT mediates direct baroreflex activation leading to descending cardiac analgesia and inversed peripheral nociception. High sensitivity to 5-HT & up-regulated 5-HT3A R in female-specific Ah-BRN are cellular mechanism of baroreflex activation. Estrogen-dependent high level of serum 5-HT & 5-HT3A R expressed in Ah-BRN leads to sex difference of cardiac nociception. Higher 5-HT3B R expression is likely to explain why no or less sensitivity to 5-HT is observed in A- and C-BRN. Clinical relevance of these findings impacts on a gender difference in silent angina and asymptomatic cardiac infarction.